Legal Protection for Children Born from Unregistered Marriage (Nikah Siri) in Indonesia: An Analysis of Constitutional Court Decision No. 46/PUU-VIII/2010 - Novita Wulan Sari; Ernu Widodo; Sri Sukma Damayanti (International Journal of Social Welfare and Family Law, 2026)
Unregistered marriage (nikah siri) in Indonesia refers to marriages conducted in accordance with Islamic religious law but not officially recorded by the state. This legal gap creates significant challenges, particularly concerning the legal status of wives, children, and marital property. This study employs a normative juridical research methodology to examine the legal consequences of unregistered marriages on the positions of wives, children, and property, as well as to analyze the forms of legal protection available for children born from such marriages. The findings reveal that wives in unregistered marriages lack legal protection comparable to those in registered marriages, including rights to marital property, alimony, and inheritance. Children born from these unions initially possess legal relationships only with their mothers and maternal families. However, Constitutional Court Decision No. 46/PUU-VIII/2010 established a legal pathway for children to establish civil relationships with their biological fathers through scientific evidence such as DNA testing. Despite this judicial development, practical implementation faces considerable obstacles including evidentiary difficulties, social stigma, and limited access to legal remedies. This research concludes that active state intervention and institutional support remain essential to safeguard children's fundamental rights, including identity, inheritance, and protection from legal and social discrimination.